DESA WONOJATI MENUJU MANDIRI LESTARI: LITERASI LESTARI,PENGOLAHAN SAMPAH,BUDIDAYA MAGGOT,ECOENZYM,DAN DIGITALISASI UMKM - Khilyatun Nisa , Nugraheni; Mochammad , Alfiansyah; Rizky Angga , Pratama; Zahra Fadia Siti , Halizah; Rega Ayu , Darasuta; Tirsa , Febiyanti; Mani'ah Mellow , Kusmiyana; Echa Putra , Prakassyah; Muhammad Daffa Alvin , Ekananda; Iftia Yasmin , Ghinnanafsi; Al Rafi Afzaal Fazl , Rab; Niken Aulia , Septiana; Chika Adinda Difia , Lestari; Erik , Kusuma (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2025)
In the issues present in the village of Wonojati, Gondangwetan District, Pasuruan, they are still related to suboptimal waste management and the low ecological awareness of the community. This situation encourages students from the Community Service Program of Jember University to implement an integrated community service program with the theme